(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
A system of nonlinear partial differential integro-differential equations with the same factor is considered. By the method of an additional argument, the existence of a unique solution to the initial problem is proved. A concrete example is considered and a solution to the problem is constructed.